Urdu ka guldasta- Nurgis - Fozia Ahsaan Farooqi (Karachi: Oxford University Press, 2021)
"Urdu Ka Guldasta: Nurgis" is an enchanting anthology that presents a curated selection of poetry and prose, showcasing the beauty and depth of Urdu literature. The collection features a diverse range of themes, including love, nature, and the complexities of human emotions, reflecting the richness of the Urdu language. Through the lens of the title "Nurgis," symbolizing beauty and resilience, the anthology captures the essence of its contributions. Each piece invites readers to explore the lyrical quality and emotional depth inherent in Urdu writing. This collection serves as an accessible introduction to the world of Urdu literature, making it a valuable resource for both seasoned readers and those new to the language, offering a delightful journey through its timeless themes and artistic expression.
"Urdu Ka Guldasta: Nurgis" is a charming collection that showcases the beauty and richness of Urdu literature through a curated selection of poetry and prose. This anthology highlights works from a variety of poets and writers, capturing themes of love, nature, and the intricacies of human experience. The title "Nurgis," often associated with the daffodil flower, symbolizes beauty and resilience, reflecting the essence of the writings within. The collection aims to celebrate the lyrical quality of Urdu while also paying homage to its cultural heritage. Perfect for both seasoned readers and newcomers, "Urdu Ka Guldasta: Nurgis" serves as a delightful introduction to the world of Urdu literature, inviting readers to immerse themselves in its timeless charm.
Keywords: Urdu Literature; Anthology